Frequency-multiplied cylindrical triboelectric nanogenerator for harvesting low frequency wave energy to power ocean observation system. (August 2022) - Jung, Hyunjun; Ouro-Koura, Habilou; Salalila, Aljon; Salalila, Marsobyn; Deng, Zhiqun Daniel
Abstract: Cylindrical triboelectric nanogenerators (C-TENGs) have been designed for low frequency wave energy harvesting. However, the random, and low amplitude and frequency of the ocean waves represent a major challenge for the operation and performance of most C-TENGs. A C-TENG must be able to operate and be triggered by any wave conditions, even in the middle of the ocean, with uniform, low amplitude, and low frequency water waves. Here, a frequency-multiplied cylindrical TENG (FMC-TENG) that uses magnets to store potential energy and instantly release it to produce high frequency kinetic energy, was designed to increase the operating frequency of the TENG using low frequency, uniform water waves and increase the power generated. A semi-analytical modeling of the FMC-TENG was performed to theoretically verify its effectiveness. Then, the electrical characteristics of the FMC-TENG were evaluated by comparison with a conventional C-TENG in a wave motion simulator. The FMC-TENG was optimized in a 12 m long water tank, and its peak power density reached 6.67 W/m 3 under a wave frequency of 0.33 Hz. Finally, an array of FMC-TENGs successfully powered an acoustic transmitter, demonstrating the ability to power an ocean observation system. Graphical Abstract: A frequency-multiplied cylindrical-TENG (FMC-TENG) was developed to efficiently harvest low frequency ocean wave energy. Our FMC-TENG converts low frequency waves into high frequency swing motion for an enhanced electrical output power. The FMC-TENG was optimized in a 12 m long water tank, and its peak power density reached 6.67 W/m 3 under a sinusoidal wave frequency of 0.33 Hz. ga1 Highlights: An innovative FMC-TENG was designed to increase the operating frequency of the TENG using low frequency ocean waves. Two-magnets mechanism was used to store potential energy and release it to produce high frequency kinetic energy. Peak power density reached 6.67 W/m 3 under a wave frequency of 0.33 Hz in a 12 m long water tank. An array of FMC-TENGs successfully powered an acoustic transmitter.